Transcriptome analysis reveals the mechanisms for mycorrhiza-enhanced salt tolerance in rice - Hsieh, Chen; Chen, Yun-Hsin; Chang, Kai-Chieh; Yang, Shu-Yi (Frontiers in Plant Science, 2022)
More than half of the global population relies on rice as a staple food, but salinization of soil presents a great threat to rice cultivation. Although previous studies have addressed the possible benefits of arbuscular mycorrhizal (AM) symbiosis for rice under salinity stress, the underlying molecular mechanisms are still unclear. In this study, we found that mycorrhizal rice had better shoot and reproductive growth. A significantly higher K+/Na+ ratio in the shoot might help mycorrhizal rice. The reactive oxygen species (ROS) scavenging capacity in rice shoots was also improved by AM symbiosis. To elucidate the molecular mechanisms required for AM-improved salt tolerance, transcriptome analysis revealing the differentially expressed genes (DEGs) based on the response to AM symbiosis, salinity or specific tissue was performed. Thirteen percent of DEGs showed tissue-preferred responses to both AM symbiosis and salt stress and might be the key genes contributing to AM-enhanced salt tolerance. Gene Ontology (GO) enrichment analysis identified GO terms specifically appearing in this category, including cell wall, oxidoreductase activity, reproduction and ester-related terms. Interestingly, GO terms related to Pi homeostasis were also found, suggesting the possible role of the Pi-related signaling pathway involved in AM-enhanced salt tolerance. Intriguingly, under nonsaline conditions, AM symbiosis influenced the expression of these genes in a similar way as salinity, especially in the shoots. Overall, our results indicate that AM symbiosis may possibly use a multipronged approach to influence gene expression similar to salinity, and this modification could help plants be prepared for salt stress.